Frontispiece: Domino Transformations of Ene/Yne Tethered Salicylaldehyde Derivatives: Pluripotent Platforms for the Construction of High sp3 Content and Privileged Architectures. Issue 69 (10th December 2019) - Sebastian, Anusha; Srinivasulu, Vunnam; Abu‐Yousef, Imad A.; Gorka, Orive; Al‐Tel, Taleb H.
Abstract : Starting material‐driven diversity‐oriented synthesis (DOS) has become an important tool for building diverse compound libraries with rich stereochemical and scaffold diversity, particularly for nature‐inspired sp 3 ‐rich non‐flat scaffolds. To this end, ene/yne tethered salicylaldehyde derivatives have emerged as a pluripotent chemical platform, the products of which led to the construction of a privileged chemical space with significant biological activities. In their review on page 15710 ff., T. H. Al‐Tel and co‐workers document various domino transformations employing o ‐alkene/alkyne tethered aryl aldehyde/ketone platforms, with emphasis on the period from 2011 to date.